“Knowledge and practice regarding essential newborn care among the primi-mothers”- A Descriptive study (International Journal of Food and Nutritional Sciences, 2023)
Newborn babies are the foundation of life, with the first week being crucial. Around 30 million babies worldwide face premature birth, low birth weight, or illness annually. In India, 50-60% of infant deaths occur within the first month, with over half happening in the first week due to a lack of neonatal care knowledge. Education and specialized care from mother and health professionals are essential to reduce mortality rates. Methodology: adopted was a quantitative, non-experimental a descriptive research design A well-structured questionnaire was used 63 primi-mothers admitted in PNC who are interested and co-operative. A non-probability purposive sampling technique was used Result: The study focused on 63 participants aged 18 to 25, with 79% falling within this range. 76% of the participants identified as Hindu. 35% completed secondary education, while 28% completed primary education. 85% were housewives, with 37% having a family income of 10,001-15,000. 97% had prior knowledge of essential newborn care, with 76% receiving information from family members and nurses. When assessing knowledge of specific components of newborn care such as feeding, cord care, thermoregulation, immunization, eye care, and kangaroo mother care, most mothers demonstrated good knowledge. Conclusion: study highlighted the importance of education and knowledge and practice in essential newborn care practices among mothers.